Еlectret properties of γ-irradiated composites of ultrahigh molecular weight polyethylene/α-SiO₂ - Magerramov, A.M.; Ismayilova, R.S.; Kuliev, M.M.; Nabiev, A.A.; Gadzhieva, E.G.; Ismayilov, J.I.; Abdullaev, R.S.; Akhundova, G.A. (Вопросы атомной науки и техники, 2018)
The influence of silicon dioxide (α-SiO₂) and the absorbed dose of γ-irradiation on the electret properties of UHMWPE+α-SiO₂ composites were studied. It is established that the dependence of the stabilized charge on the volume content of the α-SiO₂ filler has an extreme character: at 1% α-SiO₂, the charge reaches a maximum and then decreases. TSD spectra show that the thermalstability of electrets of the UHMWPE+1 vol.% α-SiO₂ composite is improved. The nature of the TSD current of the films which preliminarily γ-irradiated up to 50…100 kGy doses proves that after γ-irradiation the charges injected from corona discharge zone are mainly accumulated in the subsurface layers. However, the deterioration of the electret properties of composites irradiated at high doses of γ-irradiation is related both to an increase in electrical conductivity so, and an increase in the rate of charge relaxation.